Unhealthy foods in Nalanda, India: Consumption, perceptions, and exposure to advertisements - Samin, Sharraf; Kim, Sunny S.; Patwardhan, Sharvari; Scott, Samuel P.; Neupane, Sumanta; Chauhan, Alka; Blake, Christine E.; Gavaravarapu, SubbaRao M.; Pandey, Pooja; Menon, Purnima (CGIAR System Organization, 2023)
The Transforming Agrifood Systems in South Asia (TAFSSA) district agrifood systems assessment aims to provide a reliable, accessible, and integrated evidence base that links farm production, market access, dietary patterns, climate risk responses, and natural resource management with gender as a cross-cutting issue in rural areas in Bangladesh, India, and Nepal. It is designed to be a district-level multiyear assessment. Using data collected in FebruaryApril 2023, this data note describes the types of unhealthy foods people are eating, where they get those foods, perceptions about key unhealthy foods, and from what source they receive information about different unhealthy foods. This is one of a set of data notes that, together, provide a holistic picture of theagrifood system in the district.